En mellanneolitisk palissad i södra Halland? - Svensson (†), Magnus (In Situ Archaeologica, 2009)
In this article I propose that a site that was investigated in southern Halland on the Swedish West Coast was a Middle Neolithic palisade enclosure. The site was excavated 1991 but the remains were not fully understood. The find is of course fascinating and the implications are far-reaching if my interpretation is accepted. More work needs to be done, to confirm my suggestion. Quite a large part of the feature may be preserved outside the excavated area and renewed fieldwork is the only way to find out its extension and state of preservation. However, at present I would like to stress that it was the kind of documentation and publication, a so called technical report, which enabled my interpretation though almost twenty years have past since the actual excavation. Bearing in mind how contract archaeological excavations are published today, we may ask whether similar accomplishments will be possible in the future; or whether we will have to accept that what is not interpreted during fieldwork or in the first publications, is forever lost.